Interferon-stimulated gene 15 (ISG15): Expression profile and role in the corpus luteum of goat (Capra hircus) - JAIN, ASIT; JAIN, TRIPTI; CHANDRAKAR, KHUSHBOO; SHAKYA, SANJAY; Mukherjee, Kishore (The Indian Journal of Animal Sciences, 2022)
The corpus luteum (CL) is a dynamic and transient endocrine gland. It secretes variety of protein hormones and have an important role in survivability of the embryo during early pregnancy. Among the interferon stimulated genes (ISGs), interferon-stimulated gene 15 (ISG15) is one of the gene having important role in maintaining corpus luteum in different ruminant species, but in goat (Capra hircus) its role is not yet elucidated. In the present study, temporal expression profile of cpISG15 mRNA and protein was examined by quantitative real-time PCR (qPCR) and western blot techniques, respectively, in the CL of cyclic and pregnant does. Both cpISG15 mRNA and protein were expressed maximally in the CL during early stage of pregnancy (16 to 24 days) as compared to cyclic does. But significant difference was not found in the expression of cpISG15 mRNA and protein in the CL between the later stage of pregnancy (25 to 40 days) and cyclic does. Finding of significant upregulation of ISG15 in CL during early pregnancy at mRNA as well as protein level suggest its probable role in maintaining CL and its function at this stage in caprine.